HUBUNGAN STATUS GIZI DENGAN KESEGARAN JASMANI - Sherif Juniar Aryanto (Universitas Islam Lamongan, 2019)
In the process of learning and physical health is more emphasized in the form of physical activity that is planned systematically in order to achieve national education goals. It is intended that if the results of studying physical education and good health it can support another lesson because if students have a good fitness level it will be more enterprising and enthusiastic in following lessons. With good nutritional status will provide energy for the mediocre student in performing movement activities, while with a good level of physical fitness can support students' ability in performing daily activities without experiencing physical fatigue. The purpose of this study was to determine the correlation between nutritional status of the physical fitness of students in grade 1 at the MIS Unggulan Sabilillah Lamongan. Objectives of this study were students at the MIS Unggulan Sabilillah Lamongan first grade. Lamongan taken as many as 25 students. In this study using this type of correlational research with quantitative approach. The process of data retrieval is done by performing measurements include: age, weight, physical fitness test include: sit-ups, pull-ups, sprint 60 meters, running distance was 600 meters, and vertical jump. Based on research results: there is a significant correlation between nutritional status of the physical fitness of students in grade 1 Banjarjo Elementary School district. Padangan, with the results of significance test claim rhitung (0,621) > rtabel (0,396). The correlation between nutritional status and physical fitness levels into the category of strong correlation, where the magnitude of the correlation coefficient between the nutritional status of the physical fitness of 38,6%.